Public Debt and Stability in Economic Growth: Evidence for Latin America - Gil León, José Mauricio; Rosso Murillo, John William; Ramirez Hernández, Edgar Alonso (International Journal of Economics and Financial Issues, 2019)
We study the effect of public indebtedness on economic growth in Latin American economies. Our main findings indicate that a Public Debt-GDP ratio of 75% leads to a deceleration in growth. On the other hand, a ratio of 35% increases the growth volatility. By using a Panel VAR we also found that external shocks, such as the foreign capital flows and the terms of trade, influence in the public debt effect on the economic growth. Clearly, the higher the level of public debt, the more vulnerable the economy can be in the short term; however, in the long term the growth is relevant for fiscal sustainability. Keywords: public debt, economic growth, GDP volatility, macroeconomic stability, current account. JEL Classifications: E60, E62, H63, O47 DOI: https://doi.org/10.32479/ijefi.8167